Consensus guidelines for the management of intracranial metastases for low- and middle-income countries - Hafiza Fatima Aziz,; Saqib Kamran Bakhshi,; Zanib Javed,; Asim Hafiz,; Adeeba Zaki,; Kaynat Siddiqui,; Ahsan Ali Khan,; Mohammad Hamza Bajwa,; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement),; Syed Ather Enam, (Journal of the Pakistan Medical Association, 2024)
Metastatic tumours are among the most common types of brain tumours. However, in low- and middle-income countries (LMICs), the numbers are considerably lower. This does not necessarily indicate a decreased incidence but rather points to decreased survival rates or limited access to healthcare. The challenge of achieving better outcomes, along with associated costs and resource constraints, often hinders the effective management of brain metastasis. Even in cases where localised disease can potentially be managed to improve survival, these challenges persist. The purpose of these guidelines is to address these challenges and outline a management strategy within the context of LMICs. Keywords:Incidence, survival rate, health care, brain neoplasms, metastases, tumours